2005
DOI: 10.1016/j.pbb.2005.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clozapine and 2,5-dimethoxy-4-methylamphetamine [DOM] on 5-HT2A receptor expression in discrete brain areas

Abstract: Activation of 5-HT 2A receptors has been shown to be an essential component of the discriminative stimulus effects of indoleamine and phenethylamine hallucinogens. The objective of the present study was to determine the neuroanatomical location of the 5HT 2A receptors which may be responsible for the stimulus effects of the phenethylamine hallucinogen [−]2,5-dimethoxy-4-methylamphetamine (DOM). It was hypothesized that brain areas containing altered 5-HT 2A receptor expression in the context of a similar alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
2
7
0
Order By: Relevance
“…Previous studies reported a sizable amount of 5-HT 2A receptors in the cytosol in addition to that found in the membrane (Cornea-Hébert et al, 1999). Several reports suggest a decrease in B max with no change in K d after treatment with antipsychotics (Matsubara and Meltzer, 1989;Doat-Meyerhoefer et al, 2005). A decrease in the density of 5-HT 2A receptors without any change in affinity is consistent with the receptor internalization previously reported (Roth et al, 1995;Willins et al, 1998).…”
Section: Olanzapine Increases Rgs7 Protein Via Jak-stat Activation 137supporting
confidence: 86%
See 1 more Smart Citation
“…Previous studies reported a sizable amount of 5-HT 2A receptors in the cytosol in addition to that found in the membrane (Cornea-Hébert et al, 1999). Several reports suggest a decrease in B max with no change in K d after treatment with antipsychotics (Matsubara and Meltzer, 1989;Doat-Meyerhoefer et al, 2005). A decrease in the density of 5-HT 2A receptors without any change in affinity is consistent with the receptor internalization previously reported (Roth et al, 1995;Willins et al, 1998).…”
Section: Olanzapine Increases Rgs7 Protein Via Jak-stat Activation 137supporting
confidence: 86%
“…Several studies specifically investigated changes in the transcript level of 5-HT 2A receptors with both short-term and chronic antipsychotic treatments (Burnet et al, 1996;Doat-Meyerhoefer et al, 2005). Buckland et al (1997) reported a significant decrease in receptor mRNA in hippocampus, brain stem, and midbrain, whereas no significant change was observed in other brain regions after 32 days of treatment with the atypical antipsychotic clozapine.…”
Section: Olanzapine Increases Rgs7 Protein Via Jak-stat Activation 137mentioning
confidence: 99%
“…In addition, studies were inconclusive regarding the role for transcriptional regulation of 5-HT 2A receptor down-regulation with antipsychotics (Gray and Roth, 2001). Both, a decrease in receptor mRNA in hippocampus, brain stem, and midbrain and no change in mRNA levels are reported previously with atypical antipsychotics (Burnet, et al, 1996;Doat-Meyerhoefer, et al, 2005). Thus, transcriptional regulation of 5-HT 2A receptors by atypical antipsychotics does not appear to be responsible for down-regulation leading to the desensitization of 5-HT 2A receptor signaling.…”
Section: Discussionsupporting
confidence: 56%
“…In the PCP model, it has been shown that acute atypical drugs such as clozapine and olanzapine inhibit PCP-induced hyperlocomotion primarily due to their multiple actions on D 2 and 5-HT 2A receptors (Gleason and Shannon, 1997; Maurel-Remy et al, 1995; Millan et al, 1999). 5-HT 2A receptors may be even more important than D 2 receptors due to the fact that other 5-HT 2A antagonists such as LY53857, ritanserin, ketanserin, fananserin, and MDL 100, 907 are more effective than dopamine antagonists in suppressing PCP-induced hyperlocomotion (Gleason and Shannon, 1997; Millan et al, 1999); and repeated administration of clozapine causes a down-regulation of 5-HT 2A receptors in the prefrontal cortex (Doat-Meyerhoefer et al, 2005). Because PCP also enhances serotonergic, dopaminergic and glutamatergic neurotransmission in the nucleus accumbens and prefrontal cortex (Abekawa et al, 2007; Maurel-Remy et al, 1995; Millan et al, 1999), we have proposed that antipsychotic sensitization in the PCP-induced hyperlocomotion test is mediated by down-regulating 5- HT 2A receptors and concomitantly decreasing PCP-induced dopamine and 5-HT increases in the prefrontal cortex (Sun et al, 2009).…”
Section: Discussionmentioning
confidence: 99%